IMPLEMENTATION OF ONLINE DISPUTE RESOLUTION (ODR) AS AN ALTERNATIVE DISPUTE RESOLUTION IN TOKOPEDIA - Shella Oktaviani (Fakultas Hukum Universitas Djuanda Bogor, 2022)
Settlement out of court by means of consultation, negotiation, mediation, conciliation, or expert judgment, along with the development of the times and technology that is rapidly emerging, online dispute resolution (ODR) is an alternative to online dispute resolution. This study aims to determine the concept of